The effects of stroboscopic vision training on sports vision ability performance and punching performance in female boxers - Xiao, Y.; Gao, D.; Gao, D.; Zhuang, M.; Long, Y.; Wei, Q.; Wang, D.; Zhang, P.; Zhao, Z.; Wang, Q.; Zhang, X. (Frontiers in Physiology, 2026)
Background: Stroboscopic training uses intermittent visual occlusion to disrupt continuous visual information flow, inducing adaptive improvements in visuomotor processing. Although its efficacy has been demonstrated across several fast-response sports, its application in boxing — particularly among female athletes — remains largely unexplored. This study investigated the effects of a six-week stroboscopic training program on visual performance skills and punching accuracy in female amateur (Olympic-style) boxers, and examined the durability of training effects at a four-week follow-up.